MEMBANGUN KOMITMEN ORGANISASIONAL UNTUK MENINGKATKAN KINERJA DAN DAYA SAING ORGANISASI - ., Amin Wahyudi (Joglo, 2008)
ABSTRACT Successfulness of an organization not only depand on machine or technological, regulasi and also finansial, but rather at the human resource quality, either or quality of skill , Competency, professionality and also which not less important is an organizational commitment. Develop high komitment of human resources in a the organization will be able to conducive to various organization advantage which might not be owned by other organization, so that develop and build organizational commitment for human resources is needed absolutely if the organization like to excist and expand better Key Word : Develop Organitational Commitment , Performance,Organitational Competition